Corrigendum to "Region-wide glacier mass balances over the Pamir-Karakoram-Himalaya during 1999–2011" published in The Cryosphere, 7, 1263–1286, 2013 - J. Gardelle; E. Berthier; Y. Arnaud; A. Kääb (The Cryosphere, 2013)
No abstract available.